A tributação de criptoativos: análise jurídica e desafios da fiscalização no Brasil - Valentino, Fabio Andreata (2025)
This monograph aims to establish analytical criteria for the taxation of cryptocurrencies and cryptoassets in Brazil. There is growing concern among fiscal and treasury authorities regarding crimes such as money laundering and tax evasion committed through the uncontrolled and unregulated acquisition of cryptoassets. The topic is highly controversial, facing significant resistance from investors and implementation difficulties, given that a large portion of these virtual currencies are foreign and stored on servers located abroad. Therefore, the study of this theme is both important and contemporary, and debate on this issue should be encouraged in the national legal environment. Regarding the methodology, for the better development and presentation of this research, it is reported that, in the Investigation Phase, the Inductive Method will be used; in the Data Processing Phase, the Cartesian Method; and the results expressed in this monograph are composed on an inductive logical basis. The procedural method used was the exposition of legal, doctrinal, and jurisprudential understandings related to the central theme of the project. In the Research phases, the Techniques of the Referent, Category, Operational Concept, and Bibliographic Research were employed